Customized fertilizers for higher yield and income: Evidences from on-farm validation in coconut – tuber crop intercropping system - Byju, G.; Jaganathan, D.; Suja, G. (Journal of Plantation Crops, 2023)
Fifteen on-farm experiments were conducted in tropical tuber crops intercropped in coconut gardens in Thiruvananthapuram, Kollam and Pathanamthitta districts, Kerala, during 2018-2021 for the validation of customized fertilizers formulated from on-station developed Site-Specific Nutrient Management (SSNM) practices. The validation experiments were done under the aegis of ICAR-Central Tuber Crops Research Institute, Thiruvananthapuram, in a project funded by Coconut Development Board, Kochi, Kerala.Three treatments viz., T1: SSNM technology using customized fertilizers (CF) (SSNM), T2: present POP recommendation (POP) and T3: farmer's practice (FP) was evaluated in cassava, elephant foot yam and greater yam intercropped with coconut. System productivity and profitability were worked out for the diﬀerent treatments based on yield and income from coconut and tuber crops in the respective treatments. Pooled analysis indicated that the coconut yield under intercropping with tuber crops under SSNM using CF was higher by 12-23% in comparison to coconut monocrop maintained unscientifically by the farmers. Tuber yield under CF proved superior over POP by 9.3% and FP by 37.4%. On an average, the net income from coconut-tuber crop intercropping system under SSNM using CF was ₹ 270396 per ha, whereas it was ₹ 198047 in POP and ₹146358 in FP and significantly outperformed sole coconut (₹ 7764).Thus, the results of the validation experiments indicated that the use of customized fertilizers in tuberous intercrops oﬀered resilience with higher system productivity and profitability from coconut gardens.